ENHANCING CREATIVE THINKING THROUGH COMPUTATIONAL THINKING LEARNING STRATEGIES USING GITHUB IN VOCATIONAL SOFTWARE ENGINEERING EDUCATION FOR 11TH-GRADE STUDENTS AT STATE VOCATIONAL HIGHSCHOOL 1 OF SURABAYA (SMK NEGERI 1 SURABAYA) - Moh. Faizin; Mochammad Rizal; Moh. Rizal Adami; Mochamad Salim Ubaidillah; Mohammad Zabarzat; Muhamad Firmansyah Setiyo Nugroho; Bambang Sujatmiko; Lukman Sholeh (Adisam Publisher, 2025)
This study is a systematic literature review (SLR) on enhancing creative thinking through computational thinking learning strategies using GitHub in vocational Software Engineering (RPL) education for 11th-grade students at SMK Negeri 1 Surabaya. The objective of this article is to collect, analyze, and synthesize findings from previous studies to gain a deeper understanding of the relationship between computational thinking, GitHub, and creative thinking in vocational RPL education. The research method used in this SLR article is library research, with sources obtained from the Scopus (Elsevier) and Emerald Publishing databases. Data analysis from previous studies follows the PRISMA method. The findings indicate that creativity enhancement can be achieved through an effective curriculum. Computational thinking needs to be integrated into the curriculum to equip students with skills aligned with digital technology advancements. GitHub serves as a digital tool that fosters innovation and creativity. The study’s implications encourage schools to integrate computational thinking into the RPL curriculum to equip students with problem-solving skills relevant to digital technology developments.